(untitled) (Journal of Food and Dietetics Research, 2023)
The aim of proposed study is to evaluate the effect of textural changes on prawn chips using image analysis at various processing levels such as frying, drying and storage of the chips after 15 days. Formulations were optimized with flour combinations of 45 % wheat and 25 % refined wheat flour (Maida) and 30 % prawn flour. Drying at 60⁰C in a oven dryer followed by frying of prawn chips at 140⁰C lead to moisture removal which shows the varied intensity of brown colour in the product Depends on the intensity of brown varies with each stages of processing having strong impact on the prawn chips. Surface texture analysis were done by converting the digital image to grey scale by (GLCM) method thereby features were extracted .The changes in intensity of the grey levels can be reduced for a feature reduction which is considered to be parameter of importance. It also used as predictive tool for determining the moisture based on the grey levels. Results of moisture content 5.3%, oil uptake of 2.1 % and shrinkage after frying were16.2 %. Studies were proposed based on application of the image processing could be a rapid method for monitoring the food products.